EFFECTIVENESS OF BLENDED LEARNING WITH SOFT SKILLS IN NUMERICAL METHOD LEARNING AT THE UNIVERSITY OF BALIKPAPAN - Ismiyati, Nur; Permatasari, Besse Intan (De Fermat : Jurnal Pendidikan Matematika, 2024)
This study aims to determine the effectiveness of blended learning containing soft skills in Numerical Methods in Balikpapan University. This type of research is quantitative research with a pre-experimental experimental design, namely one group pretest-posttest design. The subject of this study was a student of Mathematics Education at Balikpapan University in the Numerical Methods course. Research instruments in the form of tests. Data analysis techniques using the Student Wilcoxon test on the learning outcome test and the t-test on N-Gain were normalized with the help of the JASP program. The results of the hypothesis test showed a value of   with , then , the results of the H0 data were rejected so that it was concluded that students could complete mathematics learning using a blended learning design with soft skills with a completeness value of 80.38 with an N-Gain score of 0.64. This means that students' ability to master numerical method subject matter is in the very good category with N-Gain values in the medium category.